Rancang Bangun Aplikasi Presensi Kegiatan Dengan Memanfaatkan NFC Sebagai RFID Reader Pada Smartphone Android - Wardani, Nur Mohamad Prima Putra; Amelia, Tan; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Institute for Business and Information Stikom Surabaya is a college which applying radio frequency technology (RFID) to support their employees and students activities. They use RFID in some aspects such as identification card, parking system, learning activities attendance logs, library gate, and non academic activities attendance logs. On non academic activities, RFID reader is used to gather participant identity and send to the server to be stored. The problem is that the current application still rely on external reader and a web based application. So, as long as there are no internet connection, the application can not be used even on Stikom local network. Based on these problems, a built-in RFID reader such an NFC on Android mobile device can be used to replace external RFID reader and an Android application which can work both on online and offline internet network.